Identifikasi Risiko Kecelakan Kerja Terhadap Pekerja Di PT. IKI Makassar Tahun 2020 (Studi Pada Pekerja Proses Marking) - Riri, Rifdah Mufiidah Rusli; A. Fachrin, Suharni; Asrina, Andi (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2020)
Introduction: Management of occupational health and safety is an integrated effort to manage the risks involved in company activities that can resulted in human injury, damage or disruption to the company's business is divided into three parts, namely Hazard Identification, Risk Assessment and Risk Control (HIRARC) aims to identify potential hazards in the workplace by linking workers, tasks, work equipment and the work environment. The purpose of this study was to identify occupational accident risk then assess the level of occupational accident risk at PT. IKI Makassar in 2020 and how to control it. Methods: The research is qualitative. The approach used in this research is a quasi-qualitative approach. The technique used is observation, in-depth interview) and documentation continuously throughout the study to analyze further about risk identification and control that can be done in the marking process at PT. IKI Makassar. Prior to qualitative research, the risk management process was measured using the HIRARC. The informants in this study were divided into three, that are key informants is the inspector K3, regular informants (part of production process management and knowing the flow of the marking production process), and supporting informants (the workers who work in part of the marking production process) at PT. IKI Makassar. Results: From the results of the study using the HIRARC (Hazard Identification, Risk Assessment and Risk Control) table, it was found that the highest potential hazards and risks were found in the marking process in cutting plates where the most frequent potential hazards such as slipping, falling, slicing and scratching. The conclusion of this research is the Potential dangers contained in the marking process at PT. Makassar IKI covers mechanical hazards in the marking area, ie pinched, dropped, scratched, sliced, knocked and crushed.